Помогите розложить **...

0 голосов
41 просмотров

Помогите розложить на множители
49с^2-(2c-15)^2
9(5a-4b)^2-64A^2
(1+x)^3-27x^3
x^2-4xy+4н:2+2х-4у
упростите выражение (
(а^2-3a)^3-a^2(a+2)(a-2)+2a(3a^2+7)


Алгебра (29 баллов) | 41 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Решите задачу:

49c^2-(2c-15)^2=49c^2-(4c^2-60c+225)= \\ 
=49c^2-4c^2+60c-225=45c^2+60c-225= \\ 
=5(9c^2+12c-45)=5(x+3)(3x-5)

9(5a-4b)^2-64a^2=9(25a^2-40ab+16b^2)-64a^2= \\ 
=225a^2-360ab+144b^2-64a^2=161a^2-360ab+144b^2= \\ 
=161a^2-84ab-276ab+144b^2=7a(23a-12b)-12b(23a-12b)= \\ 
=(7a-12b)(23a-12b)

(1+x)^3-27x^3=1+3x+3x^2+x^3-27x^3= \\ 
=1+3x+3x^2-26x^3=1+3x+3x^2-26x^3= \\ 
=1+5x-2x+13x^2-10x^2-26x^3= \\ =(1+5x+13x^2)-2x(1+5x+13x^2)= \\ 
=(1-2x)(1+5x+13x^2)

x^2-4xy+4y^2+2x-4y=x^2-2xy-2xy+4y^2+2x-4y= \\ 
=(x^2-2xy+2x)+(-2xy+4y^2-4y)= \\ =x(x-2y+2)-2y(x-2y+2)=(x-2y)(x-2y+2)

(a^2-3a)^3-a^2(a+2)(a-2)+2a(3a^2+7)= \\ 
=(a^2-3a)^3-a^2(a^2-4)+2a(3a^2+7)= \\ 
=(a^6-9a^5+27a^4-27a^3)-(a^4-4a^2)+(6a^3+14a)= \\ 
=a^6-9a^5+27a^4-27a^3-a^4+4a^2+6a^3+14a= \\ 
=a^6-9a^5+26a^4-21a^3+4a^2+14a= \\ 
=a(a^5-9a^4+26a^3-21a^2+4a+14)
(6.3k баллов)